2019
DOI: 10.3390/ijms20153689
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas Applications in Myotonic Dystrophy: Expanding Opportunities

Abstract: CRISPR/Cas technology holds promise for the development of therapies to treat inherited diseases. Myotonic dystrophy type 1 (DM1) is a severe neuromuscular disorder with a variable multisystemic character for which no cure is yet available. Here, we review CRISPR/Cas-mediated approaches that target the unstable (CTG•CAG)n repeat in the DMPK/DM1-AS gene pair, the autosomal dominant mutation that causes DM1. Expansion of the repeat results in a complex constellation of toxicity at the DNA level, an altered trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 84 publications
1
41
0
Order By: Relevance
“…Here, we are the first to report a comprehensive study on the myogenic properties of a unique series of myoblasts, which are near-isogenic and only differ in the presence of a cDM-length (CTG)2600 repeat in the DM1 locus. Our data confirm and extend the initial findings published by our own group and others on gene-edited cells in DM1 (reviewed in [27]).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here, we are the first to report a comprehensive study on the myogenic properties of a unique series of myoblasts, which are near-isogenic and only differ in the presence of a cDM-length (CTG)2600 repeat in the DM1 locus. Our data confirm and extend the initial findings published by our own group and others on gene-edited cells in DM1 (reviewed in [27]).…”
Section: Discussionsupporting
confidence: 92%
“…To investigate how the presence of a large-scale (CTG) n repeat in the mutant DMPK allele of a cDM muscle progenitor cell (referred to as parental DM11 myoblasts) influences myoblast-to-myotube formation along the path of terminal differentiation, we generated a panel of eight isogenic myoblast lines (Figure S1A). The lines were initially generated for a study of repeat instability upon the induction of dsDNA (double strand DNA) breaks up- and downstream of the (CTG) n expansion by CRISPR/Cas9 genome editing [26,27].…”
Section: Resultsmentioning
confidence: 99%
“… 36 Previous studies have demonstrated the feasibility of this approach in excising the causal CTG DNA repeat expansion in DM1 cell lines with CRISPR-Cas9 and a pair of flanking gRNAs followed by repair of the two DSBs with nonhomologous end joining albeit with variable cutting and repair efficiencies. 37 It remains to be seen whether this approach of excision of a pathogenic genomic DNA repeat is feasible in terminally differentiated cells such as corneal endothelium. Additionally, there is a risk of permanent and off-target genome editing with this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, results were presented showing that the CTG •CAG repeat can be excised by CRISPR/Cas9-mediated gene editing. After excision, corrected cDM myoblasts do show recovery in their myogenic program, but CpG hypermethylation is not reversed [24][25][26][27][28][29] .…”
Section: Session 3: Recent Advances In Genetics In Dmmentioning
confidence: 97%